Mixed Integer Programming Revealed Preference Tests of Utility Maximization and Weak Separability of Consumption, Leisure, and Money. Issue 7 (15th September 2016) - HJERTSTRAND, PER; SWOFFORD, JAMES L.; WHITNEY, GERALD A.
Abstract : Swofford and Whitney (1987, 1988, 1994) investigated the validity of two key assumptions underlying representative agent models of macroeconomics. These assumptions are utility maximization and weak separability. Using mixed integer programming, we check revealed preference conditions for these assumptions. We find that M1, money defined by Friedman and Schwartz (1963), and a broad aggregate are weakly separable. We find that consumption goods and leisure and nondurables and services are weakly separable. We find that M2, M3, and MZM are not weakly separable. Finally, we find three categories of consumption, durables, nondurables and services, do not form an aggregate.